P-035 Is bigger really better for clot ingestion during a direct aspiration first pass technique?. (22nd July 2018) - Arslanian, R; Caroff, J; Marosfoi, M; King, R; Wilson, S; Gounis, M; Chueh, J
Abstract : Introduction: Distal embolization as a result of mechanical thrombectomy during treatment of acute ischemic stroke is one of the parameters that may determine patient outcome. The aims of this study are 1) to assess the risk of distal embolization associated with varying thromboaspiration techniques in comparison to the standard balloon guide catheter assisted stent-retriever thrombectomy (BGC+SR), and 2) to understand how different extents of clot ingestion (complete vs partial) into the aspiration catheter during thromboaspiration affect the rate of first-pass recanalization. Methods: An experimental model with a circulating flow loop and cerebrovascular phantom was assembled to perform thrombectomy via BGC+SR (FlowGate, Stryker Neurovascular, Fremont, CA; Solitaire, Medtronic Neurovascular, Irvine, CA) and test aspiration efficacy of the following four catheters: the R92M 088 and 070 Reperfusion Systems (Route 92 Medical, Inc., San Mateo, CA), Penumbra ACE068 and 5MAX (054 inch internal diameter) (Penumbra Inc., Alameda, CA) (min. n=5 per group; one thrombectomy attempt per experiment). Five additional replicates per clot type were performed to elaborate findings obtained from the R92M 088 and BGC+SR groups. Two different clot types were utilized to form an MCA occlusion: a fibrin-rich hard clot supplemented with hydroxyapatite and a soft clot model with the addition of barium proven prone to fragmentation. Thromboaspiration took place once the tip of the aspiration catheter was placed proximal to the occlusion and followed by continuous aspiration for 2.5 min. Complete clot ingestion was defined as visible capture of the entire clot, whereas partial clot ingestion was a visible portion of clot outside the distal end of the aspiration catheter. Clot fragments generated during each technique were collected for particle analysis using the Coulter Principle. Results: Successful recanalization was demonstrated in 100% of cases with complete clot ingestion and in 55% of cases with partial clot ingestion. R92M 088 and BGC+SR achieved >80% recanalization rate with the hard clot, resulting in a total of 0 and 4 visible particles respectively. For the remaining devices, the recanalization rate was <20%. Both the R92M 088 and R92M 070 achieved a 100% recanalization rate with the soft clot, with 0 visible particles and an average of 3 particles sized 200–1000 µm per experiment noted. A total of 38 soft clot fragments (size range: 200–1000 µm) from 9 successful experiments were found upon observation of BGC+SR data, comparable to our previous findings (30 particles from 8 cases). 1 A higher successful rate was noted when the soft clot was used (088: 100%, 070: 100%, 068: 80%, 054: 20% and BGC+SR: 82%). No significant differences in the number of clot fragments (size: 8–200 µm) were found between the BGC+SR and R92M 088 groups, regardless of the clot type. All particulate results presented are derived from the successful recanalization cases for fair comparison. Conclusion: Both the BGC+SR and R92M 088 techniques were effective for clot removal and comparable in terms of distal embolization. The rate of first-pass successful recanalization was reduced by nearly 50% with partial clot ingestion during thromboaspiration in comparison to complete clot ingestion. Reference: Stroke 2013;44:1396–1401. Disclosures: R. Arslanian: None. J. Caroff: None. M. Marosfoi: None. R. King: None. S. Wilson: 5; C; employee of Route 92 Medical. M. Gounis: 1; C; Medtronic Neurovascular, Stryker Neurovascular, Cerenovus Neurovascular, The Stroke Project, Route 92 Medical, InNeuroCo, Mivi Neurosciences, . 2; C; Cerenovus Neurovascular, Medtronic Neurovascular, Phenox, Stryker Neurovascular, The Stroke project, Route 92 Medical, InNeuroCo, . 4; C; InNeuroCo, The Stroke Project. J. Chueh: None.